Ilmenite Inclusion: A Solution towards Solid Sagging for Hematite-Based Invert Emulsion Mud - Salem Basfar; Ashraf Ahmed; Salaheldin Elkatatny (Geofluids)
The sagging tendency of hematite in drilling mud is a common challenge occurring at high-pressure and high-temperature (HP/HT) applications. This work studies the performance of hematite-based invert emulsion mud for HP/HT conditions and provides a solution to prevent the hematite settlement using a combination of ilmenite with hematite. Practical mud formulation was utilized over a range of ilmenite/hematite ratios (0/100, 20/80, 40/60, and 50/50%) to study sagging behaviour. From the sag tests, the optimum combination proportion was determined. Thereafter, the density, emulsion stability, rheological and viscoelastic properties, and filtration conduct for the formulated mud were evaluated. The experiments were conditioned as per the standards of the American Petroleum Institute. The obtained results of sagging experiments indicated that including 50% of ilmenite mitigated the hematite settling and reduced the sag tendency towards the safe range. A slight drop (4%) in mud weight was noticed upon adding the ilmenite, whereas the emulsion stability was enhanced from 551 to 574 volts with the 50% ilmenite content. The rheology and viscoelasticity measurements showed that 50/50% combination improved the yield point (YP) by 50% with a trivial 1 cP increment on plastic viscosity (PV), hence enhancing the YP/PV ratio by 46%. Also, the gelling strength was enhanced resulting in flat rheology and better gel structure. The filtration behaviour of 50% ilmenite mud was improved compared to blank hematite as it resulted in 21, 15, and 17% reduction on the filtrated volume, filter cake weight, and thickness, respectively. This study provides a solution for hematite sagging issue at HP/HT using combined weighting agents, which contributes to enhancing the mud stability and avoiding several well control issues and related operational and technical challenges that eventually will economize the drilling cost and time.